Kanjuruhan Football Match Chaos: Media and Law Enforcement in Indonesia - Saputri, Atha Difa (Indonesia Media Law Review, 2023)
Football is a sport that is liked by many people. The game of football has fans with the name of each fan written on it. The method of writing in this research is descriptive qualitative research that aims to describe, and summarize various conditions, various situations, or various phenomena of social reality that exist in the community that is the object of research, and seeks to draw these realities to the surface as characteristics, character, nature, a model, sign, or description of a particular condition, situation, or phenomenon.The presence of supporters makes football matches more memorable and dynamic. Fan support for their favorite team often leads to over-the-top attitude. Fanaticism causes friction between different supporters. This friction led to the birth of violence among supporters. Even killed hundreds of people and injured hundreds of people. In this article, we will discuss the chronology of the Kanjuruhan incident, the parties responsible for this incident, and some of the solutions offered. As a result of this article, the Kanjuruhan incident killed 131 people and injured hundreds of others. There must be someone responsible for this heartbreaking incident and so far only six suspects have been named. Therefore, a solution is needed to prevent this incident from happening again. The solutions offered are increased literacy that must be carried out by several parties, the addition of a security team, the parties must comply with all the rules on the playing field. For victims who suffered serious injuries, all treatment has been borne by the government, and for victims who died, several parties provided compensation by the victim's family as a form of condolence.